SYNTHESIS, STRUCTURAL ELUCIDATION AND ANTIMICROBIAL EVALUATION OF 2-4-(T-AMINO)-2-(BUT-2-YN-1-YL)-1, 3 BENZOTHIAZOLE DERIVATIVES - Shafiq, Bahaa; Eldeen, Zuhair Muhi; Al-kaissi, Elham; Al-adham, Ibrahim S (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: A new series of 2-4-(t-amino)-2-(but-2-yn-1-yl)-1,3-benzothiazole derivatives, 2-[4-(pyrrolidin-1-yl)but-2-yn-1-yl]-1,3-benzothiazole (BZ2), 2-[4-(2-methylpiperidin-1-yl)but-2-yn-1-yl]-1,3-benzothiazole (BZ3), 2-[4-(piperidin-1-yl) but-2-yn-1-yl]-1,3-benzothiazole (BZ4), 2-[4-(azepan-1-yl)but-2-yn-1-yl]-1,3-benzothiazole (BZ5), 2-[4-(4-methylpiperazin-1-yl) but-2-yn-1-yl]-1,3-benzothiazole (BZ6), 2-[4-(2, 6-dimethylpiperidin-1-yl) but-2-yn-1-yl]-1, 3-benzothiazole (BZ7) were synthesized and screened in vitro as potential antimicrobial agents. Methods: In-vitro antimicrobial activity evaluation was done, by agar diffusion method and broth dilution test against Staphylococcus aureus ATCC 6538p, Candida albicans ATCC 10231, Pseudomonas aeruginosa ATCC 9027, Escherichia coli ATCC 8739, and Bacillus subtilis ATCC 6633. Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) were determined. The results of antimicrobial testing were compared to two positive control drugs ciprofloxacin (5 µg/ml) and fluconazole (500µg/ml). Results: Compound 2-[4-(azepan-1-yl) but-2-yn-1-yl]-1,3-benzothiazole (BZ5) showed the highest antibacterial activity against S. aureus with MIC value of 15.62 µg/ml while; Compound 2-[4-(2,6-dimethylpiperidin-1-yl)but-2-yn-1-yl]-1,3-benzothiazole (BZ7) exhibited the highest antibacterial activity against P. aeruginosa with MIC value of 31.25 µg/ml. Compounds 2-[4-(pyrrolidin-1-yl)but-2-yn-1-yl]-1,3-benzothiazole (BZ2) and 2-[4-(azepan-1-yl)but-2-yn-1-yl]-1,3-benzothiazole (BZ5) showed the highest antifungal activity against C. albicans with MIC value of 15.62 µg/ml (for both). Conclusion: The results obtained showed variation in the antibacterial and antifungal activity based on the structure of the cyclic amines in these amino acetylenic benzothiazole derivatives. Keywords: Benzothiazole, Aminoacetylenic, Antibacterial, Antifungal, Mannich reaction